The Diversity of the Genus Tuber in Greece—A New Species to Science in the Maculatum Clade and Seven First National Records - Vassileios Daskalopoulos; Elias Polemis; Georgios Konstantinidis; Vasileios Kaounas; Nikolaos Tsilis; Vassiliki Fryssouli; Vassili N. Kouvelis; Georgios I. Zervakis (Journal of Fungi)
Ectomycorrhizal fungi of the genus Tuber (Ascomycota) produce hypogeous ascomata commonly known as truffles. Despite their high ecological and economic importance, a considerable gap of knowledge exists concerning the diversity of Tuber species in the eastern Mediterranean region. In the frame of this study, more than 200 Tuber collections, originating from various regions of Greece, were examined. A new species to science, i.e., Tuber leptodermum, is formally described. Tuber leptodermum is grouped in the Maculatum clade, as revealed by the ITS and LSU rDNA concatenated phylogenetic tree, and appears as sister to T. foetidum. In addition, T. leptodermum exhibits distinct morphoanatomic features: it produces medium-sized, dark-brown ascomata with a thin pseudoparenchymatous peridium, composed of globose-to-angular cells and forms one-to-four-spored asci containing reticulate–alveolate, ellipsoid ascospores with broad meshes. Thirty other phylogenetic species are identified: seven of them (i.e., T. anniae, T. buendiae, T. conchae, T. dryophilum, T. monosporum, T. regianum and T. zambonelliae) constitute new records for the Greek mycobiota, while the presence of five other species is molecularly confirmed for the first time. Moreover, the existence of ten undescribed phylogenetic species is revealed, six of which are reported for the first time in Greece. Several taxonomic and phylogenetic issues and discrepancies in the genus Tuber are discussed in relation to the new findings.